EARTH OVEN DIPLOMACY: A NEW PARADIGM FOR REGIONAL COHESION - Muhammad Ilham Mustain Murda; Suwarjiya; Tindia Febriyati (Kajian Asia Pasifik, 2026)
This study aims to evaluate the effectiveness of Indonesia’s cultural diplomacy in the South Pacific region through the lens of food sovereignty and local traditions. Amidst increasing regional geopolitical complexities, this research proposes the "Earth Oven Diplomacy" framework as a potent soft power instrument that transcends the limitations of conventional, often transactional, formal diplomacy. Employing a qualitative method with a multidisciplinary approach, the study analyzes how the Bakar Batu ritual can be revitalized as an inclusive medium for strategic communication. The theoretical foundation of this research is grounded in the "Middle Power Norm Entrepreneur" concept to examine Indonesia’s strategic positioning in the region. The findings indicate that the earth oven practice is not merely a cultural artifact but a sophisticated reconciliation protocol capable of fostering trust-building and regional cohesion between Indonesia and Pacific Island nations. By adopting a localized, wisdom-based approach, Indonesia has the opportunity to position itself as an authentic actor in supporting regional stability through the Pacific Elevation vision. The study recommends the integration of Melanesian values into national foreign policy to cultivate more dignified regional relations and strengthen a collective identity as fellow Pacific nations.